User Experience Development in Elderly Heart Patient Monitoring System - Alaric Rasendriya Aniko; Tien Fabrianti Kusumasari; Sinung Suakanto; Muhammad Ivan Fadilah (This journal is published by the Department of Electrical and Information Engineering, Faculty of Engineering, Universitas Gadjah Mada., 2025)
Heart disease is a major global cause of death, particularly among the elderly. Elderly often face challenges in accessing healthcare due to physical and cognitive limitations, making remote health monitoring systems a crucial solution. However, the effectiveness of these systems depends heavily on a good user experience (UX), which is often a challenge for the elderly. This research aims to develop a user-centered design (UCD) method and design a remote patient monitoring prototype that is specifically tailored to the needs of the elderly. The research employed a design science research methodology (DSRM) and included an in-depth literature review, interviews with five elderly patients and two medical professionals, a needs analysis, and the development of the FlowBeat prototype. The developed UCD method consisted of seven phases, and its validity was assessed by six UI/UX experts using the content validity ratio (CVR) and the content validity index (CVI), including item-CVI (I-CVI) and scale-CVI (S-CVI). The results showed that the research users and test the design phases were rated as the most essential (CVR = 1) and relevant (I-CVI = 1). Conversely, the creating a personal manifesto phase scored the lowest (CVR = -0.33). The overall S-CVI score was 0.93, indicating strong content validity for most of the framework. In conclusion, the creating a personal manifesto and evaluate against requirements phases performed poorly, necessitating their removal. Furthermore, further research requires testing the prototype on elderly to ensure successful implementation in the real world.